Peningkatan Kompetensi dan Skill Petugas Statistik Diskominfo Provinsi Jambi melalui Pelatihan Penggunaan Software Mortpak dan PAST 4.03 serta Platform Canva - Bunga, Bunga Mardhotillah; Zuli Rodhiyah; Revis Asra; Zurweni; Edi Elisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The Jambi Province Communication and Information Office (Dinas Kominfo) is an agency who carry out work based on Law Number 23 of 2014 concerning Government Regions, with one of the affairs being the main task and function, namely statistical affairs sectoral. Regional Sectoral Statistics Performance refers to Presidential Regulation Number 39 of 2019 concerning One Indonesian Data (SDI), BPS Perka Number 4 of 2019 concerning the Implementation of Regional Sectoral Statistics. According to Law No. 16 of 1997 concerning Statistics, the types of statistics based on the purpose of their use consist of basic statistics which fully organized by BPS, sectoral statistics carried out by government agencies independently or together with BPS, as well as special statistics organized by institutions, organizations, individuals, and or other elements of society independently or together with BPS. Results Statistics organized by BPS are published in the Official Statistics Gazette (BRS) regularly and transparent so that the public can easily find out and or obtain the required data. Law No. 16/1997 also stipulates the establishment of the Statistical Society Forum as a forum to accommodate the aspirations of the statistical community, which is tasked with providing advice and consideration to BPS. These important points realize the implementation of the National Statistical System reliable and, effective. The role of Sectoral Statistics that must be carried out by the Ministry of Communication and Informatics is related to the provision of data development sector, assisting statistical activities in Other institutions, as well as any performance related to the methodology, education, and training in sectoral statistics. Data collection, presentation, and publication of quality data by the Ministry of Communication and Informatics, cannot be separated from the role of officers statisticians and data collectors. With regard to this Community Service (PPM) Program, the PPM Team In general, it is observed that in carrying out their work, Field Data Collecting Officers and Data Entry Officers often experience difficulties in terms of classification of data for each sector that is a priority for development, especially sectors Environment and Ecology. Entry clerks sometimes only present data individually descriptive in Ms. Excel, without being processed and without further analysis on certain software, in particular related to demographic, ecological, and environmental data. As a solution to the performance problems of Statistics/Data Collection Officers At the Jambi Province Communications and Information Office, upgrading was given in the form of training in the use of Mortpak software and training in data collection for the environmental sector and ecology.